First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Precise measurements of the cosmic ray proton energy spectrum in the “knee” region - Zhen Cao; F. Aharonian; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; C.M. Cai; W.Y. Cao; Zhe Cao; et al. (Science Bulletin, 2025)

Ocular Motor and Vestibular Profile in Spinocerebellar Ataxia Type 27B: Toward a Practical Bedside Diagnostic Framework - Leonardo Eleuterio Ariello; Daniel R. Gold; Weiyi Mu; Michael C. Schubert; Claire Allen; Ashley Paul; David P.W. Rastall (The Cerebellum, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Evidence for particle acceleration approaching PeV energies in the W51 complex - Zhen Cao; F. Aharonian; Axikegu; Y.X. Bai; Y.W. Bao; D. Bastieri; X.J. Bi; Y.J. Bi; W. Bian; A.V. Bukevich; Q. Cao; W.Y. Cao; et al. (Science Bulletin, 2024)

Opportunities and challenges in Asian bee research and conservation - Natapot Warrit; John Ascher; Parthib Basu; Vasuki Belavadi; Axel Brockmann; Damayanti Buchori; James B. Dorey; Alice Hughes; Smitha Krishnan; Hien T. Ngo; Paul Williams; Chao-Dong Zhu; et al. (Biological Conservation, 2023)

Geochemical evolution of structure-bedding controlled hydrothermal dolomites of the Kinta Valley, Western Malaysia - P. Xin Hui; R. Nagarajan; Mu. Ramkumar; T. F. Ng; Nur I. Taib; M. J. Mathew; B. Sautter; N. A. Siddiqui; M. C. Poppelreiter (Carbonates and Evaporites, 2022)
Study of secondary dolomitization and documentation of the evolution of basinal fluids and host rock, especially that of fine-grained deepwater carbonate mudstone are of interest toward of reservoir characterization. From this perspective, field characteristics in relation to mineralogy, petrography and geochemistry of the Paleaozoic carbonates of the Kinta Valley, Peninsular Malaysia, were investigated and documented. A total of 33 samples were collected across the various degree of dolomitization and analyzed for their petrographic properties ( n = 55), while mineralogical and geochemical compositions ( n = 33) were analyzed using XRD, ICP and ICPMS analysis, respectively. These analyses were performed to elucidate the diagenetic events, episodic dolomitization and development of fluid evolution as a function of regional tectono-thermal events during the Permian to Cenozoic. It is interpreted that the host calcareous mudstones (HCMs) were deposited in oxygenated, open marine seawaters. The studied samples retain the original seawater characteristics despite negligible, minor alterations of REE characteristics due to diagenesis and detrital input. Though the concentrations and trends of REEs of the dolomitic facies are modified to a certain extent, their affinities with HCMs are preserved. Enrichments of Mg, Mn, Na and depletion of Sr are linked to the effect of dolomitization under the open system of diagenesis. The redox conditions fluctuated to show distinct, recognizable variations between different dolomite phases. The MREE enrichments with other trace elements such as Mn, Fe and low Sr content indicate the association of diagenetic fluids with deep-circulating crustal hydrothermal fluids. Hydrothermal influence has been recorded along the fractures, which might have originated from the sub-surface litho units and facilitated episodic dolomitization, especially during significant tectono-thermal events. This study affirms that the occurrence, geochemical and mineralogical evolution of the dolomites of the Kinta Valley were controlled by magmatic events, whereas the intensity of replacement dolomitization was controlled by host rock texture, varied bulk chemistry of host rock, circulating fluid and temperature.

Biophysical Reviews special issue call: quantitative methods to decipher cellular heterogeneity — from single-cell to spatial omic methods - Joshua W. K. Ho; Xi Chen; Mu He; Yuanhua Huang; Jessica C. Mar; David J. H. Shih; Angela R. Wu (Biophysical Reviews, 2022)

Antidepressant Drugs Correct the Imbalance Between proBDNF/p75NTR/Sortilin and Mature BDNF/TrkB in the Brain of Mice with Chronic Stress - C. R. Yang; X. Y. Zhang; Y. Liu; J. Y. Du; R. Liang; M. Yu; F. Q. Zhang; X. F. Mu; F. Li; L. Zhou; F. H. Zhou; F. J. Meng; et al. (Neurotoxicity Research, 2020)

Assessment of the MODIS global evapotranspiration algorithm using eddy covariance measurements and hydrological modelling in the Rio Grande basin - A. L. Ruhoff; A. R. Paz; L. E. O. C. Aragao; Q. Mu; Y. Malhi; W. Collischonn; H. R. Rocha; S. W. Running (Hydrological Sciences Journal, 2013)

Nitrogen deposition in tropical forests from savanna and deforestation fires - YANG CHEN; JAMES T. RANDERSON; GUIDO R. VAN DER WERF; DOUGLAS C. MORTON; MINGQUAN MU; PRASAD S. KASIBHATLA (Global Change Biology, 2010)
We used satellite‐derived estimates of global fire emissions and a chemical transport model to estimate atmospheric nitrogen (N) fluxes from savanna and deforestation fires in tropical ecosystems. N emissions and reactive N deposition led to a net transport of N equatorward, from savannas and areas undergoing deforestation to tropical forests. Deposition of fire‐emitted N in savannas was only 26% of emissions – indicating a net export from this biome. On average, net N loss from fires (the sum of emissions and deposition) was equivalent to approximately 22% of biological N fixation (BNF) in savannas (4.0 kg N ha −1 yr −1 ) and 38% of BNF in ecosystems at the deforestation frontier (9.3 kg N ha −1 yr −1 ). Net N gains from fires occurred in interior tropical forests at a rate equivalent to 3% of their BNF (0.8 kg N ha −1 yr −1 ). This percentage was highest for African tropical forests in the Congo Basin (15%; 3.4 kg N ha −1 yr −1 ) owing to equatorward transport from frequently burning savannas north and south of the basin. These results provide evidence for cross‐biome atmospheric fluxes of N that may help to sustain productivity in some tropical forest ecosystems on millennial timescales. Anthropogenic fires associated with slash and burn agriculture and deforestation in the southern part of the Amazon Basin and across Southeast Asia have substantially increased N deposition in these regions in recent decades and may contribute to increased rates of carbon accumulation in secondary forests and other N‐limited ecosystems.

Relevance of genetically determined host factors to the prognosis of meningococcal disease - P. Domingo; E. Muiz-Diaz; M.A. Baralds; M. Arilla; N. Barquet; R. Pericas; C. Jurez; P. Madoz; G. Vzquez (European Journal of Clinical Microbiology & Infectious Diseases, 2004)

An additional 136 SSLP markers typed for the AXB and BXA recombinant inbred mouse strains - J. K. Naggert; K. L. Svenson; L. Lin; Y. -C. Cheah; P. M. Nishina; J. -L. Mu; T. R. Devereux; M. You; B. Paigen (Mammalian Genome, 1997)